The Role of Guidance and Counseling Teacher in Developing Students’ Religious Moderation Behavior at Madrasah - Ni’mah, Ulfatun; Susanti, Try; Firman, Arham Junaidi; Onia , Saifaldin Idris; Asvio, Nova (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
Abstract: Indonesia is currently facing extremism, radicalism, hate speech, and the breakdown of interfaith relations, which require that teachers fulfill their roles in developing students' religious moderation behavior. This study aims to describe the role of Guidance and Counseling teachers in developing students' religious moderation behavior at MAN Bintan. This research is classified as qualitative research when viewed from the aspect of data. The research activity was conducted at MAN Bintan from January to April 2022. The subjects for data collection in this study were Guidance and Counseling teachers. Data collection was performed through interviews, observation, and documentation. Data analysis was carried out by reducing, presenting, and verifying the data. The findings of this study demonstrate that Guidance and Counseling teachers play a central role in the development of students' religious moderation behavior at MAN Bintan, which is reflected in their roles as informants, facilitators, motivators, and mentors. Abstrak: Bangsa Indonesia sedang menghadapi ekstremisme, radikalisme, ujaran kebencian, hingga retaknya hubungan antarumat beragama sehingga guru dituntut untuk melaksanakan perannya dalam rangka mengembangkan perilaku moderasi beragama siswa. Penelitian ini mempunyai tujuan untuk mendeskripsikan peran guru Bimbingan dan Konseling dalam mengembangkan perilaku moderasi beragama peserta didik di MAN Bintan.Penelitian ini tergolong kepada penelitian kualitatif bila dilihat dari aspek datanya. Kegiatan penelitian ini dilaksanakan di MAN Bintan dari bulan Januari hingga April tahun 2022. Subyek untuk perolehan sumber data dalam penelitian ini ialah guru Bimbingan dan Konseling. Pengumpulan data terlaksana melalui kegiatan wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan reduksi, display dan verifikasi data. Temuan penelitian ini memperlihatkan bahwa guru Bimbingan dan Konseling memainkan posisi sentral dalam pengembangan perilaku moderasi beragama peserta didik di MAN Bintan yang tercermin dari perannya sebagai informator, fasilitator, motivator, dan pembimbing.